Sistem Monitoring Uang Saku Menggunakan Metode DevOps dan RFID (Radio Frequency Identification) - Aang Samsudin; Riki Darmawan (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
In the rapidly evolving digital era, the demands of modern life necessitate that parents be more productive. Busy daily lives often make it difficult for parents to directly monitor their children's activities, especially when they are at school. One of the main concerns is pocket money management. In this study, the DevOps (Development and Operations) method was used because its development cycle is easier to control, faster, and more flexible in detecting errors. Meanwhile, RFID is used to help facilitate digital transactions. As a result of this system, transactions are recorded in real time, and parents can monitor the use of their children's pocket money through the website, thereby increasing transparency, reducing waste, and facilitating financial oversight. This system also includes transactions that can be integrated with digital payments through a virtual account, allowing parents to top up their balance from home. It is hoped that this system can be an innovative solution for managing children's pocket money in educational settings.